The impact of ballot access restrictions on electoral competition: Evidence from a natural experiment - Marcus Drometer; Johannes Rincke (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
Measuring the effect of ballot access restrictions on electoral competition is complicated because the stringency of ballot access regulations cannot be treated as being exogenous to candidates' entry decisions. This paper exploits the 1968 U.S. Supreme Court decision to strike down Ohio's ballot access laws as a natural experiment to overcome the endogeneity problem. The evidence from difference-in-difference estimations suggests that the court decision and the accompanying sharp decrease in Ohio's petition requirements resulted in major parties facing a signifcant increase in competition from third party and independent candidates.
urn:nbn:de:bvb:19-epub-2922-7
Keywords: D72; D78; 330; Ballot access; Petition requirements; Electoral competition; Natural experiment; Wahlrecht; Reform; Wirkungsanalyse; Wahlkampf; Feldforschung; Ohio